Rent Subsidies on a National Basis - Elsas, M. J. (Review of Economic Studies, 1944)
Journal Article Rent Subsidies on a National Basis Get access M. J. Elsas M. J. Elsas London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 11, Issue 2, 1944, Pages 77–85, https://doi.org/10.2307/2295968 Published: 01 January 1944